A invisibilidade do trabalho do professor de língua portuguesa e literatura no curso integrado do instituto federal do Rio Grande do Sul/ campus Restinga : um enfoque ergo-dialógico - Gomes, Maíra da Silva (2021)
Every work activity, according to the ergological approach, always includes an obscure or invisible part. Debates that the worker goes through and that involve, among other issues, decision making in work situations are part of the aspects that are not very apparent, as new and unforeseen circumstances constantly appear. In this sense, the present study has the general objective of investigating aspects of the invisibility of the work activity of the Portuguese and Literature teacher of the Integrated Technical Course for High School of the Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFRS) / Campus Restinga, related to the uniqueness of teaching activity and the collective of teachers in the language area. As for the specific objectives, this research aims to examine the valuing accents of the statements made by the interviewed teachers in relation to the teaching activity, paying attention to the clashes present in the speeches that reflect and refract aspects of teaching and knowledge in adherence and in despondency; analyze dramatic self-use, debates on norms and values and renormalizations in the work of the interviewed teachers, observing the way in which each teacher is unique in the teaching activity; and verify, through dialogical relations, the approximations and distances in the speech of the interviewed teachers, observing invisible aspects of the collectivity of the teachers of the Integrated language. From the dialogical perspective of the discourse and the contributions of the ergological approach, the teachers' discourse on work activity is analyzed, glimpsing the clashes, tensions and renormalizations that are part of this work, as well as the way each teacher values its activity and to stand out in the work situation. This research is of a qualitative applied nature and its methodological procedures consist of an individual and face-to-face interview with three professors of the discipline of Portuguese Language and Literature of the Integrated course at Campus Restinga / IFRS. From the speeches produced in the interview situation, we analyze how each teacher is unique, how he values and reflects and refracts what his work involves, how he deals with new situations and how he manages the debates on norms and values. We also talked about the dialogical relations of approach and distance between the speeches of the teachers interviewed. The thesis defended in this work is the invisibility as a constitutive part of the teaching work in the Integrated, both in the individual aspect, as well as in the collective of language teachers of the Campus Restinga, considering that the area does not dialogue about the work activity and does not establish collective goals for teaching Portuguese and Literature. The results indicate that each teacher works individually and faces the tensions and struggles of the activity alone. The teacher develops his work from his own conceptions about what is teaching Portuguese and Literature, about what the Integrated course is and about what the area's function is in that course. Thus, the work of each teacher seems to be invisible to other colleagues in the field and to the institution itself.